Controlled generation of intrinsic near-infrared color centers in 4H-SiC via proton irradiation and annealing - Rühl, Maximilian; Ott, Christian; Götzinger, Stephan; Krieger, Michael; Weber, Heiko B. (Applied Physics Letters, 2018)
We report on the generation and annihilation of color centers in 4H silicon carbide (SiC) by proton irradiation and subsequent annealing. Using low-temperature photoluminescence (PL), we study the transformation of PL spectra for different proton doses and annealing temperatures. Among well reported defect signatures, we observe omnipresent but not yet identified PL signatures consisting of three sharp and temperature stable lines (denoted TS1,2,3) at 768.8 nm, 812.0 nm, and 813.3 nm. These lines show a strong correlation throughout all measurement parameters, suggesting that they belong to the same microscopic defect. Further, a clear dependence of the TS1,2,3 line intensities on the initial implantation dose is observed after annealing, indicating that the underlying defect is related to implantation induced intrinsic defects. The overall data suggest a sequential defect transformation: proton irradiation initially generates isolated silicon vacancies which are transformed into antisite vacancy complexes which are, in turn, transformed into presumably intrinsic-related defects, showing up as TS1,2,3 PL lines. We present recipes for the controlled generation of these color center
Keywords: Farbzentren

Intrinsic color centers in 4H-silicon carbide formed by heavy ion implantation and annealing - Kobayashi, Takuma; Rühl, Maximilian; Lehmeyer, Johannes; Zimmermann, Leonard; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2021)
We study the generation and transformation of intrinsic luminescent centers in 4H-polytype of silicon carbide via heavy ion implantation and subsequent annealing. Defects induced by the implantation of germanium (Ge) or tin (Sn) have been characterized by photoluminescence (PL) spectra recorded at cryogenic temperatures. We find three predominant but as-yet-unidentified PL signatures (labeled as DI1–3) at the wavelength of 1002.8 nm (DI1), 1004.7 nm (DI2), and 1006.1 nm (DI3) after high dose implantation (> 4 × 1013 cm-2) and high temperature annealing (> 1700°C). The fact that the DI lines co-occur and are energetically close together suggest that they originate from the same defect. Regardless of the implanted ion (Ge or Sn), a sharp increase in their PL intensity is observed when the implantation damage becomes high (vacancy concentration > 1022 cm-3), indicating that the lines stem from an intrinsic defect caused by the damage. By tracking the PL signals after stepwise annealing, we examine how the overall intrinsic defects behave in the temperature range of 500 – 1800○C; the silicon vacancies formed by the implantation transform into either divacancies or antisite-vacancy pairs with annealing at about 1000°C. These spectra signatures are strongly reduced at 1200°C where the so-called TS defects are maximized in luminescence. As a final stage, the DI defects, which are most likely formed of antisites and vacancies, emerge at 1700°C. Our results provide a knowledge on how to incorporate and manipulate the intrinsic luminescent centers in SiC with ion implantation and annealing, paving the way for fully integrated quantum technology employing SiC.<br

Removing the orientational degeneracy of the TS defect in 4H-SiC by electric fields and strain - Rühl, Maximilian; Lehmeyer, Johannes; Nagy, Roland; Weißer, Matthias; Bockstedte, Michel; Krieger, Michael; Weber, Heiko B. (New Journal of Physics, 2021)

Stark Tuning of the Silicon Vacancy in Silicon Carbide - Rühl, Maximilian; Bergmann, Lena; Krieger, Michael; Weber, Heiko B. (Nano Letters, 2020)
We present a versatile scheme dedicated to exerting strong electric fields up to 0.5 MV/cm on color centers in hexagonal silicon carbide, employing transparent epitaxial graphene electrodes. In both the axial and basal direction equally strong electric fields can be selectively controlled. Investigating the silicon vacancy (V-Si) in ensemble photoluminescence experiments, we report Stark splitting of the V1' line of 3 meV by a basal electrical field and a Stark shift of the V1 line of 1 meV in an axial electric field. The spectral fine-tuning of the V-Si, being an important candidate for realizing quantum networks, paves the way for truly indistinguishable single-photon sources.
CRIS-Team WoS Importer:2020-01-31